CHILD PSYCHOLOGY AND ITS IMAGE IN ART LITERATURE - H.Sharafiddinov (Scholar Express Journal, 2023)
The article shows the influence of a small territory, social, spiritual and psychological environment in the family in the formation of a person's personality in the life of children
Keywords: character; vocation; car-shop; object; individual